Evaluation of the Tropical Pacific Observing System from the ocean data assimilation perspective. (28th July 2015) - Fujii, Yosuke; Cummings, James; Xue, Yan; Schiller, Andreas; Lee, Tong; Balmaseda, Magdalena Alonso; Rémy, Elisabeth; Masuda, Shuhei; Brassington, Gary; Alves, Oscar; Cornuelle, Bruce; Martin, Matthew; et al.
Abstract : The drastic reduction in the number of observation data from the Tropical Atmospheric Ocean (TAO)/Triangle Trans‐Ocean Buoy Network (TRITON) array since 2012 has given rise to a need to assess the impact of those data in ocean data assimilation (DA) systems. This article provides a review of existing studies evaluating the impacts of data from the TAO/TRITON array and other components of the Tropical Pacific Observing System (TPOS) on current ocean DA systems used for a variety of operational and research applications. It can be considered as background information that can guide the evaluation exercise of TPOS. Temperature data from TAO/TRITON array are assimilated in most ocean DA systems which cover the tropical Pacific in order to constrain the ocean heat content, stratification, and circulation. It is shown that the impacts of observation data depend considerably on the system and application. The presence of model error often makes the results difficult to interpret. Nevertheless there is consensus that the data from TAO/TRITON generally have positive impacts complementary to Argo floats. In the equatorial Pacific, the impacts are generally around the same level or larger than those of Argo. We therefore conclude that, with the current configuration of TPOS, the loss of the TAO/TRITON data is having a significant detrimental impact on many applications based on ocean DA systems. This conclusion needs to be kept under review because the equatorial coverage by Argo is expected to improve in the future.